Organization of genes necessary for growth of the hydrogen-methanol autotroph Xanthobacter sp. strain H4-14 on hydrogen and carbon dioxide. - Lehmicke, L G (1985)
Mutants unable to grow on H2 and CO2 were isolated in the hydrogen-methanol autotroph Xanthobacter sp. strain H4-14 and complemented with a clone bank constructed in a broad-host-range cosmid vector. The mutants fell into two classes. Class I mutants (Cfx-) cannot grow on hydrogen or methanol and are deficient in one or more of the key enzymes of the Calvin Cycle. Class II mutants (Hox-) can grow on methanol but not on hydrogen and lack hydrogenase activity. Restriction maps of the complementing clones show that each class is not linked to the other. Subcloning and Tn5 mutagenesis have localized the regions of DNA complementing these mutants. The region complementing a class I mutant which is deficient in ribulosebisphosphate carboxylase activity is approximately 3.2 kilobase pairs in size. Expression of this enzyme activity from cloned DNA gave evidence for the orientation of an operon containing the structural genes for this enzyme. The region complementing most of the class II mutants is 3 to 4.5 kilobase pairs in size.